Is aripiprazole similar to quetiapine for treatment of bipolar depression? Results from meta-analysis of Chinese data - Tao, Hejian; Wang, Jiawei; Shen, Dong; Sun, Fengli; Jin, Weidong (Frontiers in Psychiatry, 2022)
Objective To study the similarities and differences in the clinical efficacy of aripiprazole and quetiapine in Chinese patients with bipolar depression through meta-analysis. Additionally, to provide evidence of aripiprazole in treatment for bipolar depression. Methods We searched Chinese literature related to the study of aripiprazole and quetiapine in treatment for bipolar depression, among which results such as comments, letters, reviews, and case reports were excluded. The clinical efficacy between aripiprazole and quetiapine was synthesized and discussed. Result A total of 1,546 subjects were included in 17 studies. The random effect model was used to review the data by RevMan 5.2. The results showed that there was no significant difference in the remission rate between patients treated with aripiprazole and quetiapine evidenced by the scale used to evaluate the patients being treated for bipolar depression (221/501 vs. 193/501, Z = 1.12, P = 0.26). But the results also showed that the remission rate of aripiprazole with lithium carbonate was significantly higher than quetiapine with lithium carbonate in the treatment of bipolar depression (111/232 vs. 69/232, Z = 3.92, P < 0.0001). The results showed that the effective rate of aripiprazole was similar to quetiapine (426/572 vs. 386/572, Z = 2.70, P = 0.007). Overall, there was no difference in the Hamilton Rating Scale for Depression (HAMD) score between patients treated with aripiprazole and quetiapine (Z = 1.68, P = 0.09). The results also show that the drop-out rate of aripiprazole was similar to quetiapine in the treatment of patients with bipolar depression (Z = 1.80, P = 0.07). Conclusion As an atypical antipsychotic, aripiprazole may be similar to quetiapine for treating bipolar depression with similar drop-out and higher remission rates when combined with lithium carbonate. However, the results of this study need to be read with caution given the poor quality of collected/analyzed literature.